Japanese fine art - Sagara, Tokuzo (Japan Travel Bureau, 1960)
The purpose of the Tourist Library Series is to give foreigners interested in Japan a basic knowledge of various phases of Japanese culture. When completed, the series is expected to include a hundred volumes or so, and will give a complete picture of Japanese culture, old and new.